Urinary Luteinizing Hormone Tests: Which Concentration Threshold Best Predicts Ovulation? - Leiva, Rene Antonio; Bouchard, Thomas Paul; Abdullah, Saman Hasan; Ecochard, René (Frontiers in Public Health, 2017)
Objective To study the best possible luteinizing hormone (LH) threshold to predict ovulation within the 24, 48, and 72 h. Design Observational study. Setting Multicenter collaborative study. Patients A total of 107 women. Interventions Women collected daily first morning urine for hormonal assessment and underwent serial ovarian ultrasound. This is a secondary analysis of 283 cycles. Main outcome measures The sensitivity, specificity, positive and negative predictive values, and positive and negative likelihood ratios were estimated for varying ranges of LH thresholds. Receiver operating characteristic curves and cost–benefit ratios were used to estimate the best thresholds to predict ovulation. Results The best scenario to predict ovulation at random was within 24 h after the first single positive test. The false-positive rate was found to increase as (1) the cycle progressed or (2) two or three consecutive tests were used, or (3) ovulation was predicted within 48 or 72 h. Testing earlier in the cycle increases the predictive value of the test. The ideal thresholds to predict ovulation ranged between 25 and 30 mIU/ml with a PPV (50–60%), NPV (98%), LR+ (20–30), and LR− (0.5). At least, one day with LH ≥25 mIU/ml followed by three negatives (LH <25) occurred before ovulation in 31% of all cycles. When used throughout the cycle and evaluated together, peak-fertility type mucus with a positive LH test ≥25 mIU/ml provides a higher specificity than either mucus or LH testing alone (97–99 vs. 77–95 vs. 91%, respectively). Conclusion We identified that beginning LH testing earlier in the cycle (day 7) with a threshold of 25–30 mIU/ml may present the best predictive value for ovulation within 24 h. However, prediction by LH testing alone may be affected negatively by several confounding factors so LH testing alone should not be used to define the end of the fertile window. Complementary markers should be further investigated to predict ovulation and identify the fertile window. The use of the peak cervical mucus along with an LH test may provide a higher specificity and predictive value than either of them alone. We recommend that manufacturers disclose their tests’ threshold to the public.